Persepsi Masyarakat Kabupaten Pati atas Televisi Digital - Choirul Ulil Albab; Alif Akbar Imron (School of Communication - Atma Jaya Catholic University of Indonesia, 2025)
The government’s policy to transition from Analogue Switch Off (ASO) to digital television has an impact on people’s information consumption patterns. This research aims to examine the influence of the level of public knowledge about digital television and the ease of accessing it on the public’s perception of digital television itself. Researchers use the Diffusion of Innovation theory. This research used quantitative methods with aspects of level of knowledge and ease of access as independent variables and public perception as the dependent variable. Data was obtained from questionnaires distributed to 100 respondents in 10 sub-districts in Pati Regency. Pati is a region located in Central Java Province, and an area where most of its population lives in rural areas. The results show that the public's perception regarding digital television is a good policy and a solution to broadcasting problems. Statistical test results show that these two variables can influence public perception of digital television by 70.1%. It shows that the transition is welcomed to contribute to a more open information distribution in society.